Empreendedorismo e economia criativa nas comunidades do Recife: análise e avaliação do projeto ressignifica do Porto Digital e British Council. - Cavalcante, Carla Guedes Porfirio (2021)
Entrepreneurship is considered by scholars as a driving force that brings economic development to localities. However, despite the great advance of programs to encourage entrepreneurial activity, both private and public, peripheral entrepreneurship still lacks attention to reach the market and provide benefits to the local community, minimizing social inequality. Thus, this dissertation had as a research problem the question: “how can programs to encourage entrepreneurship in the outskirts of cities encourage young people in social vulnerability to undertake creative businesses?”. Its objective was to analyze the impact of the Ressignifica Program on the creation, implementation and maintenance of startups by individuals in social vulnerability, residents of Recife communities. The research has an exploratory-explanatory character, since there is a need to better understand the entrepreneurial segment in question. Action research was adopted as a method, in order to gather more knowledge about the subject, through a qualitative approach. The main sources of data collection were semi-structured and indepth interviews with participants and the project coordinator, as well as documentary research in reports provided by the Porto Digital Management Center. Consequently, it was possible to go deeper into the experiences reported, to understand different nuances of the reality of the periphery. Finally, with regard to the results, the impact that the program provides for people residing in needy communities is noticeable, generating growth opportunities for this audience; it is also noticed that programs to foster peripheral entrepreneurship can provide the local development of new talents, since communities have creative individuals who need to seek new solutions for a daily life of difficulties. As a product, the dissertation culminated in the production of a minidocumentary, portraying the perception of young people about the entrepreneurial journey for those who are born and live in Recife's periphery.